Modification of benzoxazine with aryl-ether-ether-ketone diphenol: preparation and characterization. Issue 3 (5th January 2017) - Xia, Yiqing; Lin, Yifeng; Ran, Qichao; Zhu, Rongqi; Gu, Yi
Abstract : A modified benzoxazine resin system with "high strength, high modulus and high toughness" was prepared by introducing an efficient modifier ( m -DHPBP) with high catalytic activity and an aryl-ether-ether-ketone (PEEK) structure. Abstract : A highly active aryl-ether-ether-ketone diphenol intermediate ( m -DHPBP) was synthesized by molecular design. Then it was introduced into benzoxazine (BA-a) as a modifier and a new modified benzoxazine resin system (BA-a/ m -DHPBP- X ) with varying contents of m -DHPBP was prepared. Differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FT-IR) were used to characterize the curing behaviour and to explore the polymerization mechanism of the BA-a/ m -DHPBP- X mixtures by following major changes in the functional groups during the curing process. A significant reduction in the peak reaction temperature in the DSC curves and in the gel-time of BA-a/ m -DHPBP- X indicated that m -DHPBP was an effective catalyst for the ring-opening polymerization (ROP) of benzoxazine. As the amount of m -DHPBP increased, the variation in benzene ring substituents of poly(BA-a/ m -DHPBP- X ) implied that m -DHPBP reacted with BA-a and finally embedded in the three dimensional networks of poly(BA-a). The thermal properties of the BA-a/ m -DHPBP- X mixtures were evaluated by dynamic mechanical analysis (DMA) and thermogravimetric analysis (TGA); they exhibited a higher initial storage modulus, maintained a high glass transition temperature ( T g ) and displayed a higher char yield compared with the neat poly(BA-a). Furthermore, the tensile properties of poly(BA-a/ m -DHPBP- X ) were good. Thus a modified benzoxazine resin system with "high strength, high modulus and high toughness" was prepared, and a more than 60% increase in tensile strength and 78% increase in elongation at break were observed by incorporating 20 wt% m -DHPBP into poly(BA-a). We believe that this modified benzoxazine system can be applied as a matrix for high-performance composites due to its excellent processibility and superior comprehensive mechanical properties.